Fast Phthalate Detection in Textile Samples: A LC-MS/MS Screening Method Using Precursor Ion Scans - Natalia Aldegunde-Louzao; Manuel Lolo-Aira; Carlos Herrero-Latorre (Chemistry Proceedings, 2024)
Phthalate esters (PAEs), commonly known as phthalates, are widely used as plasticizers in the textile industry to improve the flexibility, transparency, and durability of various materials. However, the potential adverse health effects associated with them (such as endocrine disruption, reproductive toxicity, and possible carcinogenicity) require strict control measures. In this work, a liquid chromatography–tandem mass spectrometry (LC-MS/MS) method was developed to determine phthalates in textile samples. By using precursor ion scans (specifically the precursor ion 149, characteristic of phthalates), the procedure improved the specificity of the analysis. The developed method was successfully applied to different textile samples, and the results obtained were comparable to those from the official gas chromatography method (GC-MS/MS). The proposed method enables the rapid and effective detection of phthalates in quality control laboratories within the textile industry.